Estrategias metodológicas para la incorporación de recursos informáticos a la práctica pedagógica de los docentes del primer de bachillerato sección matutina de la Unidad Educativa Simón Bolívar de la parroquia Puerto Bolívar de la ciudad de Machala 2013-2014. - Guamán Bermeo, Jennifer Beatriz (2014)
Transcendental is that teachers know the methodological strategies that can incorporate computing resources, and the student will achieve meaningful learning, using all resources such as images, sound, interactivity, etc. The fact of incorporating computer resources into everyday life is indisputable and has been transformed into various aspects like how to learn and learn, how to search and store information, time of work and leisure, but especially the way be related.